Redesigning Inventory Management of Automotive Parts Retailers: A Case Study of Bangphaialaiyont Retailer - Wechayanwiwat, Duangkamol (2010)
In today’s business the numerous automotive parts retail businesses have been increased significantly in Thailand. These new retailers have adopted advanced technologies or efficient techniques to manage their inventories so as to attain the competitive performance. A case study, Bangphaialaiyont is one of auto parts retailers, which has confronted inventory problems for many years. This paper identifies the major root causes of high percentage of absent stocks and excessive stocks problem, focuses on the utilisation of inventory models which can eliminate these root causes by applying to three families of auto parts namely fast moving, slow moving and seasonal products, proposes the implementation of Enterprise Resource Planning (ERP) system used to develop and redesign inventory management of this retailer, and suggests the further beneficial systems or techniques to significantly improve competitive performance. Diagnosis of this inventory problem already carried out in form of the fishbone diagram, analysis of inventory model adoption is examined in three distinct parts, including (s, Q) system for fast moving products, (R, S-1, S) system for slow moving products, and Newsvendor model for seasonal products, and then eventually the most important findings and additional recommendations are highlighted. With regard to redesigning inventory management, it is concluded that the combination of inventory models application and ERP implementation results in managing inventory more efficiently, thus the business owner enables to obtain huge profitability such as eliminating root causes of inventory problems, reducing enormous inventory costs, and maintaining the high level of customers’ satisfaction. In the future, the business may extend to looking into benchmarking strategy and barcode system utilised to develop substantially inventory management. This may be of particular interest to the owner of Bangphaialaiyont retail business or other automotive parts retailers who are deciding to develop their inventory management. In addition, this would assist to further researchers who study for retail business cases of the inventory models selection or ERP implementation.